Advances in integrative structural biology: Towards understanding protein complexes in their cellular context - Samantha J. Ziegler; Sam J.B. Mallinson; Peter C. St. John; Yannick J. Bomble (Computational and Structural Biotechnology Journal, 2021)
Microorganisms rely on protein interactions to transmit signals, react to stimuli, and grow. One of the best ways to understand these protein interactions is through structural characterization. However, in the past, structural knowledge was limited to stable, high-affinity complexes that could be crystallized. Recent developments in structural biology have revolutionized how protein interactions are characterized. The combination of multiple techniques, known as integrative structural biology, has provided insight into how large protein complexes interact in their native environment. In this mini-review, we describe the past, present, and potential future of integrative structural biology as a tool for characterizing protein interactions in their cellular context.